Study guide for pharmacology for nursing care - Lehne, Richard A. (Maryland Heights, Missouri : Elsevier Saunders, 2013)
Includes critical thinking study questions, case studies, and patient teaching scenarios that connect pharmacology concepts with their impact on patient care.
Chapter 1. Orientation to Pharmacology -- Chapter 2. Application of Pharmacology in Nursing Practice -- Chapter 3. Drug Regulation, Development, Names, and Information -- Chapter 4. Pharmacokinetics -- Chapter 5. Pharmacodynamics -- Chapter 6. Drug Interactions -- Chapter 7. Adverse Drug Reactions and Medication Errors -- Chapter 8. Individual Variation in Drug Responses -- Chapter 9. Drug Therapy During Pregnancy and Breast-Feeding -- Chapter 10. Drug Therapy in Pediatric Patients -- Chapter 11. Drug Therapy in Geriatric Patients -- Chapter 12. Basic Principles of Neuropharmacology -- Chapter 13. Physiology of the Peripheral Nervous System Cholinergic Drugs -- Chapter 14. Muscarinic Agonists and Antagonists -- Chapter 15. Cholinesterase Inhibitors and Their Use in Myasthenia Gravis.
Keywords: PHARMACEUTICAL PREPARATIONS